2019
DOI: 10.1177/2050313x19876710
|View full text |Cite
|
Sign up to set email alerts
|

Congenital sideroblastic anemia associated with B cell immunodeficiency, periodic fevers, and developmental delay: A case report and review of mucocutaneous features

Abstract: This is a 40-year-old woman with sideroblastic anemia with B cell immunodeficiency, periodic fevers, and developmental delay syndrome, who has genital and extragenital lichen sclerosus on the abdomen and the upper back that have become erythematous and painful during febrile episodes. This report summarizes the published cases of sideroblastic anemia with B cell immunodeficiency, periodic fevers, and developmental delay and highlights associated mucocutaneous features.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 12 publications
1
13
0
Order By: Relevance
“…A later review of the 17 cases previously reported in the literature did not evidence consistent mucocutaneous manifestations in SIFD. However, one adult patient presented lichen sclerosus et atrophicus and morphea (6). Panniculitis, but not relapsing erythema nodosum, was previously reported in one SIFD patient (7).…”
Section: Discussionmentioning
confidence: 85%
“…A later review of the 17 cases previously reported in the literature did not evidence consistent mucocutaneous manifestations in SIFD. However, one adult patient presented lichen sclerosus et atrophicus and morphea (6). Panniculitis, but not relapsing erythema nodosum, was previously reported in one SIFD patient (7).…”
Section: Discussionmentioning
confidence: 85%
“…Etanercepet started at 2 y still ongoing after 8 y Alive at 10 years. After Eta starting resolution of fever and associated symptoms 45 [ 5 ] Homozygous: c.218_219ins22 NA Exon 3 frameshift 0 m RBC transfusions & Immunoglobulin replacement 2 of 3 patients reported by Fouquet died 46 [ 5 ] Compound heterozygous: c.668 T.C p.I223T Exon 6 Missense c.829G > T; p.Glu277* Exon 7 0 m RBC transfusions & Immunoglobulin replacement 2 of 3 patients reported by Fouquet died 47 [ 5 ] Homozygous: c.977 T.C p.I326T Exon 7 Missense 12 m RBC transfusions & Immunoglobulin replacement 2 of 3 patients reported by Fouquet died 48 [ 18 ] Homozygous: c.977 T.C p.I326T Exon 7 Missense Neonatal RBC transfusions & Immunoglobulin replacement Alive at 4 years old 49 [ 19 ] Compound heterozygous: c.668 T.C p.I223T Exon 6 Missense c.1057-7C.G NA Intron 7 Splicing infancy Around 12 m) Immunoglobulin replacement Alive at 42 years 50 [ 20 ] Compound heterozygous: c.295C > T R99W Exon 3 Missense c.1234C > T, p.Arg412X Exon 8 Stop 1 m Immunoglobulin replacement Alive at 12 years old 51 [ 21 ] Heterozygous: c.448C > T,p.R150C Exon 4 Missense 3 m Short course of methylprednisolone Etanercept at 5 years of age Alive at 64 months with an improvement of quality of life after Etanercept starting. The child had no further febrile episodes or seizures 52 [ 22 ] Compound heterozygous: c.525delT; ...…”
Section: Resultsmentioning
confidence: 99%
“…Vomiting, diarrhoea and hepatic disease diseases were described in 38/58 (65%) patients, especially during fever episodes and 5 experienced an exocrine pancreatic insufficiency [ 1 5 , 8 10 , 14 – 19 , 23 , 29 ]. Partial villous atrophy or acute and chronic inflammation in bowel mucosa was recorded in 5 patients [ 3 , 4 , 9 , 19 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations